BERNARD'S PERSEVERANCE AND AMBITION TO GO AGAINST RACIAL DISCRIMINATION TO ACHIEVE HIS SUCCESS, THE BANKER (2020) - Simanjuntak, Revida Engelbetha; Wulandari, Tri (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This thesis is entitled Bernard Perseverance and Ambition to go Against Racial Discrimination to Achieve His Success in George Nolfi's movie, The Banker (2020). Three questions to be answered in this thesis: What kind of racial discrimination was experienced by Bernard? How does Bernard fight against racial discrimination in society and get his success? Furthermore, what are the reasons behind Bernard's perseverance and ambition to become a successful banker?This thesis aims to analyze the racial discrimination black people in America experience and how it affects their psychological side. The writer uses approaches and theories from Henry and Tator, Dahrendorf, Duckworth, and Adler to describe how racial discrimination happens in society and its effect on the people who face it. The qualitative approach is applied, and the descriptive method is used in this thesis. The result shows that racial discrimination has a significant effect on the black people in America who face the limited rights of citizens due to government laws that tend to support the majority of the race, whites. The qualitative approach is applied, and the descriptive method is used in this thesis. The result shows that racial discrimination has a significant effect on the black people in America who face the limited rights of citizens due to government laws that tend to support the majority of the race, whites.